2021
DOI: 10.1155/2021/5596924
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota‐Related Effects of Tanhuo Decoction in Acute Ischemic Stroke

Abstract: Acute ischemic stroke (AIS) is a major cause of acquired adult disability and death. Our previous studies proved the efficacy and effectiveness of Tanhuo decoction (THD) on AIS. However, the therapeutic mechanism remains unclear. We recruited 49 AIS patients and 30 healthy people to explore the effects of THD+basic treatment on the poststroke gut microbiota of AIS patients using 16S rRNA sequencing, in which 23 patients received basic treatment (control group) and 26 patients received THD+basic treatment (THD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 53 publications
(70 reference statements)
1
32
0
Order By: Relevance
“…In order to solve phlegm-heat syndrome, we created a Tanhuo decoction (THD) with the effects of clearing heat, removing phlegm, and eliminating turbid. The decoction is combined with WM treatment to improve both the TCM syndromes and neurological deficits (Guo et al, 2021). We also found that THD has the effects of antiinflammation, antiplatelet aggregation, and reducing fibrinogen (Song et al, 2019b).…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…In order to solve phlegm-heat syndrome, we created a Tanhuo decoction (THD) with the effects of clearing heat, removing phlegm, and eliminating turbid. The decoction is combined with WM treatment to improve both the TCM syndromes and neurological deficits (Guo et al, 2021). We also found that THD has the effects of antiinflammation, antiplatelet aggregation, and reducing fibrinogen (Song et al, 2019b).…”
Section: Introductionmentioning
confidence: 65%
“…To illustrate the underlying mechanisms of the ITCM treatment at the microbial level, we analyzed the gut microbiota data before and after treatment. Our previous study observed a better improvement of several beneficial bacteria after ITCM treatment than after WM treatment (Guo et al, 2021). In the current study, we evaluated the effects of ITCM in different gut enterotypes.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Calorie restriction also can promote ischemic stroke rehabilitation via enriching the abundance of Bifidobacterium (73). Tanhuo decoction also promoted poststroke recovery by decreasing the biosynthesis of TMA, the precursor of TMAO, and increasing the expression of trimethylamine-corrinoid protein Co-methyltransferase (mttB), which catabolizes TMA to methane (69). Additionally, Lactulose supplementation was shown to significantly improve the functional outcome of stroke, which is possibly mediated by repairing intestinal barrier injury and improving gut microbiota dysbiosis following stroke (75).…”
Section: Ischemic Strokementioning
confidence: 99%